Effects of planting density of rubber tree clone RRIM 2020 clone and RRIM 2025 clone wood to particleboard properties - Abdul Halip, Juliana; Osman Al-Edrus, Syeed SaifulAzry; Lee, Seng Hua; Md Tahir, Paridah; Mohd Yunus, Nor Yuziah; Salit, Mohd Sapuan; Rushdan, Ahmad Ilyas (Tech Science Press, 2022)
The depletion of log resources encourages research into alternative ways to sustain the wood supply. Therefore, the 4-year-old Rubber Research Institute of Malaysia (RRIM) clones series, RRIM 2020 and RRIM 2025, were chosen as potential raw materials for particleboard in this study. The purpose of this study was to assess the effects of planting density and rubber tree clones on the mechanical and physical properties of single-layer particleboard. The planting densities used were low, moderate-low, moderate-high, and high, representing 500, 1000, 1500, and 2000 trees/ha, respectively. Prior to manufacturing, the RRIM 2000 series clone trees were harvested, cut, chipped, flaked, and screened. The mechanical and physical properties were evaluated in accordance with the Japanese Industrial Standard (JIS A 5908-2003). The findings revealed that both planting density and clone had a signifi- cant impact on the mechanical and physical properties of particleboard with a thickness of 10 mm and a density of 700 kg/m3 . RRIM 2020 specimens with low planting density had superior modulus of elasticity (MOE), modulus of rupture (MOR), and internal bonding (IB) values of 2415, 19, and 1.7 MPa, respectively. Furthermore, moderate-low planting density demonstrated the lowest thickness swelling (TS) and water absorption (WA) values and was comparable to control particleboard from commercial clone Prang Besar (PB), PB260. In terms of rubber clones, RRIM 2020 particleboard met the minimum requirements of the JIS standard for mechanical properties and outperformed RRIM 2025. This study recommended a low planting density of 500 trees/ha and the RRIM 2020 clone as a suitable raw material for particleboard manufacturing with a ten percent urea formaldehyde resin content.